Kinetodynamic Model and Simplified Model of X-Type Seat System with an Integrated Spring Damper - Changcheng Zhou; Leilei Zhao; Yuewei Yu; Fuxing Yang; Song Wang (Shock and Vibration)
A simplified analytical model with transformation coefficients of X-type seat system with an integrated spring damper for control strategies development is proposed on the basis of a kinetodynamic model. Firstly, based on a commercial seat of trucks, the relationship between the suspension support force and the spring force was created by using virtual work principle. The analytical formulae of the equivalent stiffness Ke and the stiffness transformation coefficient ρk were deduced. Based on the principle of conservation of energy, the analytical formulae of the equivalent damping coefficient Ce and the damping transformation coefficient ρc were deduced. Then, the motion equation of the simplified model was created. Secondly, the nonlinear dynamic equation of a complex seat model including the kinematic characteristics was established. Thirdly, the road test was conducted using a heavy truck to collect the seat vibration signals. Finally, the simplified model was validated by the tested data and compared with the complex model. The results show that the accuracy of the simplified model is acceptable. Moreover, the influence laws of kinematic parameters on ρk and ρc were revealed. The proposed simplified model provides an accurate and efficient tool for designing controllable seat suspension system that minimizes a necessary tuning process.